Representation Mathematics through The Power of Two - Pangestuti, Hutami Diana; Syaf, Agus Hikmat; Rachmawati, Tika Karlina (Pusat Studi Pengembangan Pembelajaran Matematika, 2021)
Mathematical representation is one of the abilities that support students in understanding mathematical concepts. However, some students have difficulty in developing mathematical representation skills so that it needs good handling so that the objectives of learning mathematics are achieved. The purpose of this study was to describe the improvement of students' mathematical representation abilities in mathematics learning using “The Power of Two” model. Researchers used a quantitative approach with the method of Quasi Experiment and Pretest-Posttest Control Group Design. The population in this study were students of class X one of the high schools in Bandung Regency, the sample was taken by simple random sampling technique. The selected sample was class X MIPA-4 as the experimental class and X MIPA-5 as the control class. The instruments used were in the form of description questions to obtain N-Gain data and student responses to obtain response data regarding mathematics learning through the Power of Two model. The data analysis technique used is the Independent t-Test. The results showed that the average increase in the mathematical representation ability of students who received mathematics learning using The Power of Two model was 0.88 in the high category, while the average increase in the mathematical representation ability of students who received conventional learning was 0.67 in the moderate category. That is, there are differences in the increase in the mathematical representation ability of students who learn using The Power of Two model with students who learn using conventional models. In general, 87.5% of students gave positive responses to learning mathematics using the Power of Two model. Thus, learning mathematics through The Power of Two model can improve students' mathematical representation abilities.